Phasicity and resistance of the arterial spectral Doppler waveform in a canine femoral focal artery stenosis model. (December 2022) - Zhao, Rui; Zheng, Haining; Wang, Wei; Du, Yigang; Tong, Yisha; Mahé, Guillaume; Wen, Chaoyang
Introduction: This study aims to evaluate changes in the arterial spectral Doppler waveform in a canine artery stenosis model. Methods: Canine femoral artery stenosis models were established in 12 beagle dogs. Doppler waveforms were recorded in the femoral artery preoperatively and postoperatively in the femoral artery and at the ankle after formation of a 50%, 70%, and 90% stenosis or occlusion. Major descriptors for arterial Doppler waveform were used to analyse waveforms. Results: The proportion of multiphasic waveforms proximal to a moderate stenosis decreased compared to normal baseline, although the difference was not statistically significant, whereas the decreases at the stenosis, distal to the stenosis, and at the ankle were significant ( p < 0.05). The decreases in arteries with a more severe stenosis or occlusion were significant at all locations ( p < 0.05). The proportion of high resistive waveforms decreased significantly at the ankle in the arteries with a moderate stenosis (50%) ( p = 0.002), but the decreases proximal to, at, and distal to the stenosis were not significant. The decreases were significant at all locations in the arteries with a more severe stenosis ( p < 0.05). The decrease was significant at the ankle in the arteries with an occlusion ( p < 0.001) but not significant pre, at, and post an occlusion. Conclusions: Phasicity and resistance of Doppler waveforms alter in canine femoral arteries with a stenosis. Phasicity change seems more sensitive in response to an arterial stenosis than resistance change. Additional information on arterial resistance could be obtained using end-diastolic ratios, resistive indices, and potentially end-systolic notch velocity measurements.